Puerarin Ameliorates Caerulein-Induced Chronic Pancreatitis via Inhibition of MAPK Signaling Pathway - Zeng, Xiang-Peng; Zeng, Jing-Hui; Lin, Xia; Ni, Yan-Hong; Jiang, Chuan-Shen; Li, Da-Zhou; He, Xiao-Jian; Wang, Rong; Wang, Wen (Frontiers in Pharmacology, 2021)
Pancreatic fibrosis is one of the most important pathological features of chronic pancreatitis (CP), and pancreatic stellate cells (PSCs) are considered to be the key cells. Puerarin is the most important flavonoid active component in Chinese herb Radix Puerariae, and it exhibited anti-fibrotic effect in various fibrous diseases recently. However, the impact and molecular mechanism of puerarin on CP and pancreatic fibrosis remain unknown. This study systematically investigated the effect of puerarin on CP and pancreatic fibrosis in vivo and in vitro. H&E staining, Sirius Red staining, qRT-PCR and Western blotting analysis of fibrosis and inflammation related genes of pancreatic tissues showed that puerarin notably ameliorated pancreatic atrophy, inflammation and fibrosis in a model of caerulein-induced murine CP. Western blotting analysis of pancreatic tissues showed the phosphorylation level of MAPK family proteins (JNK1/2, ERK1/2 and p38 MAPK) significantly increased after modeling of cerulein, while puerarin could inhibit their phosphorylation levels to a certain extent. We found that puerarin exerted a marked inhibition on the proliferation, migration and activation of PSCs, determined by CCK-8 assay, transwell migration assay, scratch wound-healing assay and expression levels of α-SMA, Fibronectin, Col1α1 and GFAP. Western blotting result demonstrated that puerarin markedly inhibited the phosphorylation of MAPK family proteins (JNK1/2, ERK1/2 and p38 MAPK) of PSCs in a dose-dependent manner whether or not stimulated by platelet-activating factor. In conclusion, the present study showed that puerarin could be a potential therapeutic candidate in the treatment of CP, and the MAPK pathway might be its important target.